DAMPAK KEPEMIMPINAN NEHEMIA DAN RELEVANSINYA DENGAN GEREJA-GEREJA DI JAWA TENGAH - Sentot Purwoko; David Ming; Christian Ade Maranatha (Sekolah Tinggi Teologi Moriah, 2020)
The church in terms of organization and communication systems cannot be separated from the leadership of God's servants, because leaders have an influence on the growth and development of the organization in the church. The role of a successful leader in organization and communication is critical. The formulation of the problem posed by the author is: the success of implementing leadership based on the book of Nehemiah for God's servants in churches throughout Central Java? Is the character of dependence on God the most dominant character modeled by God's servants in churches throughout Central Java? Which background category is the most dominant in determining the success of implementing the leadership of God's servants based on Nehemiah's book for God's servants at GKKI throughout Central Java. The author uses a quantitative descriptive method with an explanation method for the type of correlation review. Is the successful implementation of leadership based on the book of Nehemiah for God's servants in churches throughout Central Java in the sufficient category? Is the dimension of depending on God as Nehemiah's most dominant character in the role modeled by God's servants in churches throughout Central Java in carrying out successful leadership based on the Book of Nehemiah proven true? Gereja dalam pengertian organisasi dan sistem komunikasi tidak dapat dipisahkan dari kepemimpinan hamba-hamba Tuhan, kerena para pemimpin mempunyai pengaruh terhadap pertumbuhan dan pengembangan organisasi di gereja. Peranan pemimpin yang berjaya dalam organisasi dan komunikasi sangat penting. Rumusan masalah yang ditimbulkan oleh penulis adalah: keberhasilan pelaksanaan kepemimpinan berdasarkan buku Nehemia untuk hamba-hamba Tuhan di gereja-gereja di seluruh Jawa Tengah? Apakah watak bergantung pada Tuhan merupakan watak paling dominan yang dimodelkan oleh hamba-hamba Tuhan di gereja-gereja di seluruh Jawa Tengah? Kategori latar belakang mana yang paling dominan menentukan keberhasilan pelaksanaan kepemimpinan hamba-hamba Tuhan berdasarkan buku Nehemia untuk hamba-hamba Tuhan di GKKI di seluruh Jawa Tengah. Penulis menggunakan kaidah deskriptif kuantitatif dengan kaidah penjelasan jenis tinjauan korelasi. Apakah pelaksanaan kepemimpinan yang sukses berdasarkan kitab Nehemia untuk hamba-hamba Tuhan di gereja-gereja di seluruh Jawa Tengah berada dalam kategori yang mencukupi? Apakah dimensi bergantung kepada Tuhan sebagai watak Nehemia yang paling dominan dalam peranan yang dimodelkan oleh hamba-hamba Tuhan di gereja-gereja di seluruh Jawa Tengah dalam melaksanakan kepemimpinan yang sukses berdasarkan Kitab Nehemia terbukti benar?